NMR-based Metabolomic Analysis of Human Bladder Cancer - CAO, Ming; ZHAO, Liangcai; CHEN, Haige; XUE, Wei; LIN, Donghai (Analytical Sciences, 2012)
Bladder cancer (BC) is one of the most common cancers and has a high mortality rate. However, both metabolite variations and metabolic pathways related to the pathogenic process of BC remain to be addressed, such results might contribute to early detection of the disease. 1H nuclear magnetic resonance (NMR)-based metabolomics was applied to identify differences of serum metabolic profiles among BC, calculi patients and healthy subjects. Serum metabolic profiles of BC patients are distinctly different from those of calculi and healthy subjects. Compared with those from healthy subjects, serum samples from BC patients show decreased levels of isoleucine/leucine, tyrosine, lactate, glycine, citrate, as well as increased levels of lipids and glucose. The results reveal disturbed metabolic pathways of aromatic amino acids, glycolysis and citrate cycle, as well as lipogenesis metabolism in BC patients. Our work will be of potential benefit to understanding the pathogenic process of BC and will offer valuable information for noninvasive diagnosis of the disease.